(untitled) (Research, Society and Development, 2020)
Enteroparasitosis is a serious public health problem in Brazil and worldwide, being caused by parasites such as helminths that cause nutritional damage and can lead the host to death. The drugs used in the treatment of helminthosis can act in several ways, however, the options of these drugs on the market are still limited. Ascaridol is known to have great pharmacological potential in anti-bacterial, anti-fungal, anti-viral and anti-neoplastic therapies. Thus, this work aims to evaluate the anthelmintic activity of Ascaridol through an in silico study. As methodology, the free software Pass Online® was used to analyze the probability of the molecule’s activity. Ascaridol demonstrated a good result for the probability of activation (Pa) in relation to the values of the probability of inactivation (Pi) in the anthelmintic and nematode anthelmintic activities. It is concluded that this monoterpene had a high potential as an anthelmintic, however, in vitro and in vivo studies in greater diversity of helminthic species and in toxicological tests are still necessary in order to clarify its safety and therapeutic index.